Synthesis of Activated Carbon from Coffee Bean Skin to Reduce BOD in Liquid Waste from Rambak Cracker Industry - Rahayu, Beby Putri; Amaria (Helium: Journal of Science and Applied Chemistry, 2025)
Liquid waste from the rambak cracker industry in Tulungagung primarily contains organic compounds that can lead to high levels of Biological Oxygen Demand (BOD). The objectives of this study were: 1) to determine the characteristics of activated carbon from coffee bean skins synthesized from coffee bean skins with different concentrations of H3PO4 activator. 2) to determine the effect of activated carbon mesh size on BOD levels of liquid waste from the Rambak Cracker Industry. Activated carbon from coffee bean skins was synthesized with H3PO4 as an activator at 5, 10, and 20% concentrations, with a 200-mesh size. The synthesis results were compared with liquid waste from the rambak cracker industry to determine the difference in BOD levels. The quality of activated carbon was analyzed in accordance with SNI 06-3730-1995, including water content, ash content, volatile matter content, bound carbon content, iodine absorption capacity, and functional groups. The results of the characterization of 200 mesh coffee bean skin activated carbon obtained water content of 5.00; 5.04; 5.18%, ash content of 3.37; 3.28; 2.62%, volatile matter content of 37.78; 36.67; 35.08%, bound carbon content of 53.85; 55.01; 57.12% and iodine absorption capacity of 998.51; 1011.21; 1023.9 ​​mg/g. The results of functional group identification by FTIR showed that the functional groups detected in activated carbon were aliphatic CH, C=O, C-C, C=C, and C-O. BOD levels before and after contact with activated carbon were 2841.15 and 355.23 mg/L. The study concluded that 200-mesh coffee bean skin-activated carbon with a 20% H3PO4 activator can reduce BOD levels in liquid waste from the Rambak cracker industry by 87.5%.